Risk factor analysis associated with neospora caninum in dairy cattle in western brazilian amazon - Venturoso, Poliana de Jesus Souza; Venturoso, Osvaldo Juliatti; Silva, Gisele Glomba; Maia, Maerle Oliveira; Witter, Rute; Aguiar, Daniel Moura; Pacheco, Richard de Campos; Ferreira, Elvino; da Costa, Alvimar José [UNESP]; Dos Santos-Doni, Thais Rabelo (FapUNIFESP (SciELO), 2021)
Neospora caninum is considered to be one of the main causes of abortion among cattle. The present survey was conducted in the municipality of Rolim de Moura, Rondônia State, Brazil. A questionnaire that investigates the epidemiological aspects of neosporosis was used in the analysis of risk factors associated with the animal-level and herd-level prevalence in dairy cattle. A total of 416 bovine blood samples were collected from 30 farms, and N. caninum antibody levels were measured by Indirect Fluorescent Antibody Test (IFAT). Analysis of dairy cattle serum samples revealed the presence of anti-N. caninum antibodies to be 47.36% (n = 197). Risk factors associated with N. caninum infection were the management system and access locations of dogs. The results of the present survey indicated that infection of dairy cattle with N. caninum is widespread in the studied region of Western Amazon, which has implications for prevention and control of neosporosis in this region. Therefore, integrated control strategies and measures are recommended to prevent and control N. caninum infection in dairy cattle. In addition, direct contact between dairy cattle, dogs and wild animals, which can influence the epidemiology of neosporosis, should be investigated further.
Análises de fatores de risco associado a neospora caninum em gado leiteiro na amazônia ocidental brasileira
Keywords: Brazil; Neosporosis; Prevalence; Risk factors; Western Amazon